2015
DOI: 10.1159/000430495
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Long-Term Study on the Efficacy and Safety of UV-Free Blue Light for Treating Mild Psoriasis Vulgaris

Abstract: Background: Blue light irradiation reduces the proliferation of keratinocytes and modulates T-cell immune response in vitro and has been shown to reduce the severity of psoriasis vulgaris (Pv) in two clinical trials. Objective: Evaluation of safety and efficacy of long-term UV-free blue light treatment at home for mild Pv. Methods: Forty-seven patients with mild Pv were randomized for receiving high-intensity blue light treatment (HI: 453 nm LED, 200 mW/cm2, n = 24) and low-intensity treatment (LI: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
89
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(101 citation statements)
references
References 21 publications
2
89
0
10
Order By: Relevance
“…Application of visible and NIR light for therapeutic purposes covers a whole spectrum of cutaneous interventions across both cosmetic and medical domains. Examples include removal of vascular and pigmentary lesions [6], unwanted hair [7], and tattoos [8] to wound healing [9], scar resurfacing [10], skin rejuvenation [11,12], and stimulation of hair growth [13][14][15], treatment of psoriasis and eczema [16,17] and more [18]. Effective therapeutic modalities, which rely on all five types of light-tissue interactions (plasma ablation, photodisruption, photoablation, photothermolysis and photochemical reactions), and where the impact of photons on tissue depends on the wavelength, optical power density and exposure time [19], have already been very successfully embraced by a range of professional and home-use devices [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Application of visible and NIR light for therapeutic purposes covers a whole spectrum of cutaneous interventions across both cosmetic and medical domains. Examples include removal of vascular and pigmentary lesions [6], unwanted hair [7], and tattoos [8] to wound healing [9], scar resurfacing [10], skin rejuvenation [11,12], and stimulation of hair growth [13][14][15], treatment of psoriasis and eczema [16,17] and more [18]. Effective therapeutic modalities, which rely on all five types of light-tissue interactions (plasma ablation, photodisruption, photoablation, photothermolysis and photochemical reactions), and where the impact of photons on tissue depends on the wavelength, optical power density and exposure time [19], have already been very successfully embraced by a range of professional and home-use devices [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…In dermatology, application of PBM spans the cosmetic and medical fields including androgenetic alopecia 7, 8 , alopecia areata 9 , skin rejuvenation 10 , wound healing 11 and alleviation of psoriasis vulgaris and atopic dermatitis symptoms 12, 13 , where many commercialized professional and home-use devices exist 3, 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Additional evidence in this respect came from in vitro studies using HaCaT cells, where gene expression analysis showed downregulated pathways implicated in inflammatory responses, and using dendritic cells, where a reduced ability to release pro‐inflammatory cytokines was shown . At the clinical level, the recently reported positive impact of blue light on alleviating symptoms of psoriasis vulgaris (PV) and atopic dermatitis (AD), chronic inflammatory skin diseases characterized by hyperproliferation and inflammatory infiltrates, holds promise for its therapeutic potential …”
Section: Introductionmentioning
confidence: 99%